Presenteeism at the workplace - Claus Schnabel (IZA World of Labor, 2022)
Many workers admit that at times they show up for work even though they feel sick. This behavior, termed "presenteeism," is puzzling since most workers do not incur financial losses when staying home sick. The various reasons behind presenteeism are person-related (e.g. individuals' health or job attitude) or work-related (e.g. job demands and constraints on absence from work). Working when sick can have positive and negative consequences for workers' performance and health, but it also affects co-workers' well-being and firms' productivity. There are various strategies as to how firms can address presenteeism.
Keywords: I1; I12; I14; J24; 330; presenteeism; sickness; health; productivity